Implementasi Supervisi Akademik Kepala Sekolah di SMP Negeri 5 Gunungkencana - Karim, Abdul (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2024)
The aim of this research is to determine the implementation of the principal's academic supervision at SMP Negeri 5 Gunungkencana. This research uses a descriptive qualitative approach. Data was obtained from the Banten Province BPMP supervision instrument. The supervision instrument consists of a Learning Implementation Plan (RPP), learning process, and assessment. The sample for this research was eight teachers consisting of five female teachers and three male teachers with varying subject expertise. The curriculum used is the 2013 Curriculum. In the RPP aspect, almost all teachers have made complete RPPs even though they are not yet systematic, although there is one teacher who has made RPPs systematically but not yet complete. In the aspect of the learning process, all teachers have carried out the learning process well starting from the introductory, core, and closing activities. Finally, in the assessment aspect, all teachers have carried out assessments in accordance with the three domains (cognitive, affective, and psychomotor) of the 2013 Curriculum. It can be concluded that teachers at SMP Negeri 5 Gunungkencana have carried out learning well. It is hoped that the results of this supervision can become an illustration and reference for related parties, especially school principals, to improve teacher performance.